Peran Digital Komunikasi Terhadap Perempuan Berwirausaha (UMKM) di Kota Padang - Erna Susanti; Fitri Firdalius; Purwanti Endah Rahayu (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
Presently, development of technology has affected to all our activities, especially on business. The research aims to determine the role and the influence of digital communication for women entrepreneurs (MSMEs) productivity in Padang. The method of the research is qualitative descriptive with descriptive qualitative analysis. The result showed that digital communication has important role for women entrepreneurs (MSMEs) in Padang. It provides additional market share, accessibility of promotion and increases of women entrepreneurs (MSMEs) productivity.